Challenging the Mississippi Fire Bombers : Memories of Mississippi 1964?65. - Dann, Jim (Baraka Books, 2013)
In June 1964, courageous young civil rights workers risked their lives in the face of violence, intimidation, illegal arrests, and racism to register as many African American voters as possible in Mississippi, which had historically excluded most blacks from voting. With a firsthand account of the details and thoughtful descriptions of key people on the front lines, including Fannie Lou Hamer, Charles McLaurin, John Harris, Irene McGruder, and many more, author Jim Dann brings that historic period back to life. He places those 15 months in Mississippi-known as Freedom Summer-in the overall.